2005
DOI: 10.1158/0008-5472.can-04-4422
|View full text |Cite
|
Sign up to set email alerts
|

Tid1 Negatively Regulates the Migratory Potential of Cancer Cells by Inhibiting the Production of Interleukin-8

Abstract: Tid1 is the human homologue of the Drosophila tumor suppressor, Tid56. Reducing the expression of Tid1 in MDA-MB231 breast cancer cells enhanced their migration without affecting their survival or growth rate. From microarray screening, we discovered that after Tid1 depletion, the mRNA level of interleukin-8 (IL-8) was significantly increased in these cancer cells, which consequently increased secretion of IL-8 protein by 3.5-fold. The enhanced migration of these Tid1-knockdown cells was blocked by reducing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 30 publications
3
31
1
Order By: Relevance
“…3A). As recently reported, the expression of IL-8 was associated with enhanced migratory potential and invasiveness of metastatic breast cancer cells (33 shown in Fig. 3B, conditioned media from H 2 O 2 -treated cells induced migration of MCF-7 cells in a time-response manner, whereas pre-treatment with G. lucidum inhibits oxidative stress-induced migration in a dose-response manner.…”
Section: G Lucidum Suppresses Oxidative Stress-induced Secretion Of supporting
confidence: 84%
“…3A). As recently reported, the expression of IL-8 was associated with enhanced migratory potential and invasiveness of metastatic breast cancer cells (33 shown in Fig. 3B, conditioned media from H 2 O 2 -treated cells induced migration of MCF-7 cells in a time-response manner, whereas pre-treatment with G. lucidum inhibits oxidative stress-induced migration in a dose-response manner.…”
Section: G Lucidum Suppresses Oxidative Stress-induced Secretion Of supporting
confidence: 84%
“…Here, we selected IL-8 for further analysis among the predicted targets of miR-520b because it can modulate cancer cell migration and metastasis through several signaling pathways, such as phosphatidylinositol 3-kinase and Rho-GTPases (17,20,39). We confirmed the correlation between IL-8 expression and migration of breast cancer cells (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Recently, increasing evidence has suggested that chemokines, such as IL8, S100A8, CXCL14, and CCL5, produced by stromal cells surrounding tumors are associated with tumor development and progression via cross-talk between tumor and stromal cells. IL8 has been shown to play important roles in angiogenesis and metastasis (38), and neutralization of IL8 by an anti-IL8 antibody has been shown to inhibit angiogenesis, tumor growth, and metastasis in malignant melanoma (39). One recent report found that S100A8 secreted by a distant primary tumor could attract Mac 1(+)-myeloid cells to the premetastatic lung, suggesting that S100A8 plays a role in long distance metastasis (40).…”
Section: Discussionmentioning
confidence: 99%